Age-related inflammatory biomarkers in early-onset osteoporosis in females with Gaucher disease - Ivanova, Margarita M.; Dao, Julia; Kasaci, Neil; Huang, Fang; Nguyen, Emily; Goker-Alpan, Ozlem (Frontiers in Endocrinology, 2025)
Gaucher disease (GD), the most common lysosomal disorder, is caused by a deficiency of the enzyme glucocerebrosidase (GCase). Accumulation of the substrate, glycosylceramide (Gb-1), and its lysosomal derivative, glucosylsphingosine, Lyso-Gb1, are associated with immune-mediated inflammation. Patients with GD experience progressive bone disease, including early-onset osteoporosis (OSR). Bone marrow infiltration with Gaucher cells and reduced bone mineral density (BMD) suggest that glycosphingolipids affect hematopoiesis, osteoclast differentiation and activity. Unlike the general population, where osteoporosis is a concern later in life, females with GD have an increased risk of BMD loss starting from adolescence, which is further impacted by pregnancy, breastfeeding, and menopause. The study’s aim was to investigate immune and inflammatory markers, focusing on early-onset osteoporosis in females. GD females and healthy controls were categorized by age: pre-menopause (<45), 45-55, and post-menopause (55+), and were further divided into three sub-cohorts: no bone complications, osteopenia (OSN), and osteoporosis (OSR). The Luminex Cytokine-96-Plex panel analysis identified 26 elevated cytokines. CD40L, APRIL, IL-35, and MIP-3β were correlated with age in healthy females but were elevated in all age categories in GD. Increased levels of Eotaxin, MCP-1, and CCL27 (CTACK) correlated with OSR. Furthermore, the age-related macrophage inflammatory protein (MIP-3β) was associated with BMD loss in female patients with GD.ConclusionThis study highlights that the ongoing release of cytokines associated with immune aging may contribute to early-onset osteoporosis in GD. By identifying age- and disease-specific cytokine signatures, including elevated levels of CD40L, APRIL, MCP-4, Eotaxin, STACK, and MIP-3β, we propose a pathophysiological link between inflammation and early-onset osteoporosis in female patients with GD.